2013
DOI: 10.1002/adfm.201300936
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Organization of Inkjet‐Printed Organic Semiconductor Films Prepared in Inkjet‐Etched Microwells

Abstract: The high‐precision deposition of highly crystalline organic semiconductors by inkjet printing is important for the production of printed organic transistors. Herein, a facile nonconventional lithographic patterning technique is developed for fabricating banks with microwell structures by inkjet printing solvent droplets onto a polymer layer, thereby locally dissolving the polymer to form microwells. The semiconductor ink is then inkjet‐printed into the microwells. In addition to confining the inkjet‐printed or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 33 publications
0
47
0
1
Order By: Relevance
“…S7). In comparison, other patterning methods used to create patterned OSCs for isolated OTFTs have shown relative variances ranging from 20% to 84% (9,15,17,22,31,32,35,42,(48)(49)(50)(51)(52)(53)(54). For example, Li et al (15) have shown that using a PMMA:C8BTBT blend on a solution wetting pattern can deposit crystal plates that have a mobility relative variance of >40%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7). In comparison, other patterning methods used to create patterned OSCs for isolated OTFTs have shown relative variances ranging from 20% to 84% (9,15,17,22,31,32,35,42,(48)(49)(50)(51)(52)(53)(54). For example, Li et al (15) have shown that using a PMMA:C8BTBT blend on a solution wetting pattern can deposit crystal plates that have a mobility relative variance of >40%.…”
Section: Resultsmentioning
confidence: 99%
“…To address the above challenges, various groups have developed methods to pattern OSCs (3,9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), such as templating OSCs (14,(19)(20)(21), inkjet printing (9,18), gravure printing, and other roll-to-roll coating methods (25)(26)(27). In addition, the use of solvent wetting/dewetting surface treatments has been widely used in conjunction with the patterning methods described above (10, 11, 13, 15-17, 22, 28, 29).…”
mentioning
confidence: 99%
“…Thus, inkjet technology has been regarded as an effective fabrication tool for the use of liquid functional materials and has been implemented into research areas such as fabrication of organic thin-film transistors [2], organic solar cells [3], 3D structures [4], and cellular structures [5]. The properties (i.e., viscosity, surface tension, and density) of the printing liquids govern the operation of an inkjet printing system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this effect can be suppressed by careful solvent selection or optimised printing parameters [16]. Although the coffee ring effect is usually seen as undesirable, useful applications have been demonstrated such as microwells [22], microelectromechanical relays [23] and narrow features [24]. It has been shown that the coffee ring effect can lead to thin and uniform films in the centre of a feature [18,20].…”
Section: Introductionmentioning
confidence: 99%